The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1104/pp.49.5.672
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ethylene Action

Abstract: Deuterated ethylene was used to study the mechanism of ethylene action in etiolated pea seedlings (Pisum sativum L. cv. Alaska). No apparent differences were observed in the biological activity of tetradeuteroethylene (CGD4) and ordinary ethylene (C2H4) using the pea stem straight growth assay. The absence of an isotopic effect is discussed in relation to the possibility that ethylene binds to a metal or that carbon to hydrogen bonds of ethylene are broken during its mechanism of action.Analyses by gas chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…It has been concluded that ethylene binds to a metal-containing receptor having limited access of approach, with a Km = 6 X 10-10 M (45). The binding must be through a noncovalent bond for no exchange of deuterium occurs when deuterated ethylene is applied to responsive plants (58,59). The transient nature of the binding is also revealed by the fact that many responses to ethylene are rapidly reversible; for example growth inhibition in the etiolated pea stem (Fig.…”
Section: Mechanism Of Ethylene Actionmentioning
confidence: 96%
“…It has been concluded that ethylene binds to a metal-containing receptor having limited access of approach, with a Km = 6 X 10-10 M (45). The binding must be through a noncovalent bond for no exchange of deuterium occurs when deuterated ethylene is applied to responsive plants (58,59). The transient nature of the binding is also revealed by the fact that many responses to ethylene are rapidly reversible; for example growth inhibition in the etiolated pea stem (Fig.…”
Section: Mechanism Of Ethylene Actionmentioning
confidence: 96%
“…analysis as before showed glycine (49 mol yo) and a trans: cis ratio of 93 : 7. For (5), 8(D,O, 2H decoupled) 1.19(1 H, d, J 7.7 Hz), and 1.34(1H, d, J 7.7 Hz). We have shown that the presence of glycine does not affect ethylene production from apples.…”
mentioning
confidence: 99%